2017
DOI: 10.3892/ol.2017.5571
|View full text |Cite
|
Sign up to set email alerts
|

FosB transcription factor regulates COX-2 expression in colorectal cancer cells without affecting PGE2 expression

Abstract: Abstract. The expression levels of cyclooxygenase (COX)-2 and the prostaglandin E2 (PGE2) content have been associated with poor prognosis in patients with colorectal cancer (CRC). There is a strong correlation between COX-2 expression and PGE2 production in tissues from CRC patients, suggesting an important role for COX-2 on the regulation of PGE2 production. Previous studies by the present authors, where CRC patients were divided into high-or low-COX-2 expressing tumors, displayed important differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Assays for the binding of 3 H-labeled glutamate (PerkinElmer, Stockholm, Sweden) to the MCs (1 × 10 6 cells) were performed in 1.5-ml microcentrifuge tubes using 100 nM 3 H-labeled glutamate (specific activity = 48.6 Ci/mmol) for different incubation periods (5,20,40,60, and 180 min) at 4°C. Incubation in the absence or presence of excess unlabeled glutamate (50 µM) was followed by the addition of 3 H-labeled glutamate.…”
Section: H-glutamate Binding Assaymentioning
confidence: 99%
“…Assays for the binding of 3 H-labeled glutamate (PerkinElmer, Stockholm, Sweden) to the MCs (1 × 10 6 cells) were performed in 1.5-ml microcentrifuge tubes using 100 nM 3 H-labeled glutamate (specific activity = 48.6 Ci/mmol) for different incubation periods (5,20,40,60, and 180 min) at 4°C. Incubation in the absence or presence of excess unlabeled glutamate (50 µM) was followed by the addition of 3 H-labeled glutamate.…”
Section: H-glutamate Binding Assaymentioning
confidence: 99%
“…The three top up and down regulated genes in the CLOs vs primary cell lines were TFF3, PLEKHB1, LTB and FOSB, CAV1, AHNAK2, respectively. Interestingly, FOSB is a proto-oncogene, and CAV1 expression has been linked with mammary tumorigenesis and increased lung metastasis 47,48 . AHNAK2 has also previously been found to be upregulated in PDAC 49 .…”
Section: Discussionmentioning
confidence: 99%
“…This dedifferentiation theory is supported by a previous study which has shown that when implanted orthotopically, organoids recapitulate tumour progression from precursor PanIn lesions to metastatic carcinoma 25 . Interestingly, genes down regulated in PDX tumour/organoids and CLOs include genes which have increased expression in cancers, including potential PDAC biomarkers (CYR61, PLAU, FOSB, ECM1, LIF, GJB3 and CAV1) 48,49,[57][58][59][60][61][62] . There is also an increased expression of tumour suppressor genes LRIG1 and SEMA3F 55,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase (COX)-2 plays crucial roles in the metabolism of arachidonic acid to PGE2. Therefore, COX-2 is well known to be positively associated with carcinogenesis, malignant aggressiveness, and poor outcomes in many types of malignancies [7][8][9] . However, pathological activities of PGE2 are not always dependent on COX-2 because various other factors besides COX-2 regulate PGE2 production 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we should know the facts that the binding of PGE2 to its speci c receptor, E-prostanoid receptor (EP), is essential to exsert pathophysiological functions of PGE2 [14]. The EP receptor family consists of four isoforms (EP1-4 receptor), and the interactions between PGE2 and EP receptors in malignancies vary depending on cell type and tumor-surrounding conditions 5,7,15,16 .…”
Section: Introductionmentioning
confidence: 99%